Profile of Nurse Managers in Turkey: A Descriptive Study - Nilgün Göktepe; Oya Çelebi Çakıroğlu; Devrim Eren Tekin; Azime Uslu; Mine Ayşen Aksoy; Hanife Tiryaki Şen; Nihal Ünaldı Baydın; Sevim Şen; Ülkü Baykal (Sağlık ve Hemşirelik Yönetimi Dergisi, 2022)
Aim: This study aims to reveal the current profile of personal and professional characteristics of nurse managers in Turkey. Method: The sample of this descriptive and cross-sectional study consisted of 1.222 nurse managers in Turkey. The data were collected through an online questionnaire and analyzed using descriptive statistics in SPSS 24.0 program. Results: Most of the nurses between the ages of 20-62 are married (74.7%) and have children (72.9%), take care of their children depending more on family support (49.3%), 64.9% owned a house and 62.9% owned a car. Of all, 43.6% have a bachelor's degree, 76.4% have a degree in nursing, and 30.9% are working in public hospitals and the position of first-line nurse manager (59.7%). The mean duration of professional experience of the nurse manager was 17.04+-7.67 and the mean duration of managerial experience was 7.40+-6.24. Most of them chose the nursing profession willingly (77.1%) and working with high performance (80.6%) was effective in becoming managers. More than half of the participants were not members of any professional organization (64.2%) or a trade union (67.5%), had not received any training in management (57.4%) or orientation training for managerial positions (57.9%). It has been determined that they are willing to participate in the management courses to be organized (91.7%), they mostly follow the legal regulations related to nursing (63.4%), and attend nursing-related congresses (53.3%) to support their professional and managerial development. Conclusion: This research provides important data in terms of identifying the personal and professional characteristics of nurse managers in Turkey and revealing their needs and expectations regarding their professional training and career development.